Energy-efficiency upgrades : principles, details, examples - Richarz, Clemens (Detail practice., 2007)
"These guidelines for energy-conscious and sustainable refurbishment are intended to encourage the inclusion of energy-related themes in the design considerations for upgrading measures, but also new building work. Large-scale detail drawings illustrate practical solutions for overcoming weaknesses in the construction. Energy efficiency is investigated in terms of the different situations in summer and winter." "But sustainable improvements cannot be achieved through energy-efficiency measures alone. Instead, it is essential to consider the building as a whole, and this fact becomes clear in this book, especially through the case studies. Each example of a housing, office or school project includes an analysis of the situation plus a description and evaluation of the measures implemented."--Jacket